Boundedness for Hardy Type Operators on Herz Spaces with Variable Exponents (Analysis in Theory and Applications, 2014)
In this paper, we will prove the boundedness of Hardy type operators $H_{β(x)}$ and $H^{*}_{β(x)}$of variable order $β(x)$ on Herz spaces $K^{α(·)}_{p(·), q}$and $\dot{K}^{α(·)}_{p(·), q}$, where $α(·)$ and $p(·)$ are both variable.
Keywords: Herz spaces; Hardy type operators; variable exponent.